GAMBARAN PERILAKU PERSONAL HYGIENE PADA REMAJA SAAT MENSTRUASI DI MASA NEW NORMAL DI KOTA PEKABARU - Alfi, Natasya Raisha (Jurnal Kesehatan Ilmiah Aufa Royhan, 2022)
Adolescents at puberty experience important changes regarding the maturity of body functions which are marked by the occurrence of menstruation. The genital organs, during menstruation, are very susceptible to bacterial infections. One way to avoid the genital organs from health problems is to practice personal hygiene behavior during menstruation. This study aims to determine the description of personal hygiene behavior in adolescents during menstruation in the new normal period. This study is a quantitative study with a descriptive design to describe the description of personal hygiene behavior in adolescents during menstruation in the new normal period. The measuring instrument used is a modified questionnaire and has been tested for validity and reliability. The research sample amounted to 343 people who could meet the inclusion criteria. The analysis used is a simple descriptive analysis. The results showed that there were 180 respondents who had personal hygiene behavior during menstruation in the positive category (51.4%) with the majority of positive behavior in the aspect of genital organ hygiene (65.1%), while the majority of negative behaviors were in the aspect of using sanitary napkins (41, 4%). It can be concluded that the description of personal hygiene behavior in adolescents during menstruation in the new normal shows positive behavior. This research is expected to be one of the information regarding personal hygiene behavior in adolescents during menstruation